Antinuclear antibodies (ANA) as a criterion for classification and diagnosis of systemic autoimmune diseases - Andrade, Luis Eduardo C.; Damoiseaux, Jan; Vergani, Diego; Fritzler, Marvin J. (Journal of translational autoimmunity (Online), 2022)
The classification and diagnosis of systemic autoimmune diseases are frequently based on a collection of criteria composed of clinical, laboratory, imaging, and pathology elements that are strongly associated with the respective disease. Autoantibodies are a distinctive hallmark and have a prominent position in the classification criteria of many autoimmune diseases. The indirect immunofluorescence assay on HEp-2 cells (HEp-2 IFA), historically known as the antinuclear antibody test, is a method capable of detecting a wide spectrum of autoantibodies. A positive HEp-2 IFA test is part of the classification criteria for systemic lupus erythematosus (SLE) and juvenile idiopathic arthritis (JIA), as well as the diagnostic criteria for autoimmune hepatitis (AIH) and primary biliary cholangitis (PBC). A positive HEp-2 IFA test can appear as different morphological patterns that are indicative of the most probable autoantibody specificities in the sample. Only some of the HEp-2 IFA patterns are associated with the specific autoantibodies relevant to SLE, JIA, AIH, and PBC, whereas some other patterns occur mainly in non-related conditions and even in apparently healthy individuals. This paper provides a critical review on the subject and proposes that the classification and diagnostic criteria for SLE, JIA, AIH, and PBC could be improved by a modification on the HEp-2 IFA (ANA) criterion in that the staining patterns accepted for each of these diseases should be restricted according to the respective relevant autoantibody specificities. •Autoantibodies play a prominent role in the classification or diagnostic criteria of many autoimmune diseases.•ANA test is part of the classification criteria for SLE and JIA, as well as the diagnostic criteria for AIH.•Different HEp-2 IFA patterns indicate different autoantibodies and only some are associated with a specific disease.•ANA classification/diagnostic criteria should reflect the HEp-2 IFA patterns associated to the relevant autoantibodies.